2006
DOI: 10.1108/10222529200600009
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal capital structure: a practical contemporary approach

Abstract: Determining an optimal capital structure for a company is a multi-facetted problem that has challenged and fascinated academics and practitioners for a long time. This study investigates capital structures used in different countries and industries and explores the different theories on capital structure that have been put forward to date. A trade-off model, incorporating taxes and financial distress costs, is applied to determine the optimal capital structure for three companies listed on the JSE South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…Bhayani (2006) studied the impact of leverage on shareholder’s return in the Indian cement industry. De Wet (2006) studied the relationship between firm value and optimal gearing level. Fama and French (2002) found a positive relationship between leverage and profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bhayani (2006) studied the impact of leverage on shareholder’s return in the Indian cement industry. De Wet (2006) studied the relationship between firm value and optimal gearing level. Fama and French (2002) found a positive relationship between leverage and profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the previous literature, financial leverage has been selected as a component of risk and of capital structure [See 13, [14][15][16][17]. Furthermore, another body of research examined financial leverage as a significant indicator representing capital structure in the study of internal control mechanisms [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…De Wet (2006) has demonstrated that firms select target leverage ratios based on a trade-off between the benefits and costs of increased leverage This target leverage ratio is influenced by three factors: tax, financial distress costs and agency costs. Managers will therefore choose the combination of debt and equity that achieves a balance between the benefits of debt (tax advantage) and the various costs associated with debt (financial distress costs and agency costs) (De Wet, 2006). These three factors are discussed in more detail to demonstrate how they could affect the capital structure.…”
Section: Trade-off Theorymentioning
confidence: 99%
“…Therefore, when a firm includes too much debt in its financing mix, the financial distress costs will significantly increase. The impact of these increased financial distressed costs will increase the risk of bankruptcy, which will cause a decrease in the overall value of a firm (De Wet, 2006).…”
Section: Financial Distress Costsmentioning
confidence: 99%